Allogeneic donor split skin grafts for treatment of refractory ulcers in cutaneous chronic graft-versus-host disease after allogeneic hematopoietic stem cell transplantation—a retrospective analysis on seven patients - Lamby, P.; Wolff, D.; Mielke, Stephan; Grigoleit, G. U.; Ljungman, P.; Hilgendorf, Inken; Holler, E.; Holler, B.; Weber, D.; Herr, W.; Schiltz, Daniel; Klein, S.; et al. (Annals of Hematology, 2019)
Refractory skin ulcers due to severe chronic graft-versus-host disease (cGVHD) remain to be associated with significant morbidity and mortality. We performed an allogeneic donor skin transplantation in seven adult patients after allogeneic hematopoietic stem cell transplantation for cGVHD-associated refractory skin ulcers. While four patients received a split skin graft (SSG), in one patient, a full thickness skin graft for two small refractory ulcers of the ankle was performed, and one patient received in vitro expanded donor keratinocyte grafts derived from hair roots of the original unrelated donor. In one additional patient, a large deep fascial defect of the lower leg was covered with an autologous greater omentum free graft before coverage with an allogeneic SSG. An additional patient was treated with an autologous scrotal skin graft for a refractory ulcer associated with deep sclerosis of cGVHD after unrelated donor transplantation. All skin grafts engrafted and resulted in permanent coverage of the grafted ulcers without any signs of immunological mediated damage. In the patient receiving in vitro expanded keratinocyte grafts, two localized ulcers were permanently covered by donor skin while this approach failed to cover extensive circular ulcers of the lower legs. Allogeneic donor skin grafts are a valuable treatment option in refractory ulcers due to cGVHD but are restricted mainly to related donors while keratinocyte grafts from unrelated donors remain experimental. In male patients lacking a related donor, autologous scrotal skin graft may be an alternative option.
CRIS-Team Scopus Importer:2023-03-23
Keywords: Allogeneic hematopoietic stem cell transplantation; Chronic graft-versus-host disease; Cutaneous ulcers; Skin grafts